A Process Analysis of Message Style and Persuasion: The Effects of Gain-Loss Framing and Emotion-Inducing Imagery. Issue 3 (3rd July 2019) - Seo, Kiwon; Dillard, James Price
Abstract : An experiment ( N = 455) was conducted to examine the persuasive effects of two stylistic elements: gain-loss framing and emotionally evocative imagery. The theoretical model specified that perceived message valence is a direct result of the two elements and that valence subsequently influences emotional and cognitive responses and ultimately behavioral intention. With two positive, attractive message topics (free travel to the Caribbean and free tablet PC), three message conditions varied the coupling of frame and image (matched, mismatched, and no image). Results from structural equation modeling largely indicate that gain framing with matched image led to stronger effects on mediators and persuasion.